The impact of Chinese value - customer Ren orientation on harmony, business relationship, service quality and loyalty - Lee, Bernard (2016)
This thesis presents an empirical study of the effects of Customer Ren Orientation on Harmony, Business Relationship, Service Quality and Loyalty in the context of Chinese culture. Ren is a deeply embedded Chinese value in Chinese society. Actually, using Ren to deal with conflicts in various situations in the Chinese community is common. Nowadays, Chinese culture of Ren seems to emerge as a genuine gap that needs to be further investigated for the following reasons. Ren tends to affect business relationships between customers and service providers and consumers’ evaluations of these relationships. Clearly, the research gap is not about having a new model for cultural values but about understanding the identified Chinese cultural value of Ren that affects business practice.